A new baenid turtle from the early Paleocene (Torrejonian) of New Mexico and a species-level phylogenetic analysis of Baenidae. (16th June 2016) - Lyson, Tyler R.; Joyce, Walter G.; Lucas, Spencer G.; Sullivan, Robert M.
Abstract: New cranial and postcranial material of the baenid turtle Neurankylus from the Paleocene Nacimiento Formation (Torrejonian NALMA) of northwestern New Mexico represents a new species, Neurankylus torrejonensis . The material consists of a fragmented but mostly complete skull, a partial carapace and plastron, portions of both humeri, a partial pelvis, a complete right femur, and a distal phalanx. The small, undivided cervical scale, wide vertebrals, complete ring of marginals, and large size (carapace length 520 mm) diagnose the new taxon as belonging to Neurankylus . The narrow fifth vertebral scale and scalloped posterior shell margin reveal affinities with Neurankylus baueri Gilmore, 1916, which is known from Campanian sediments in New Mexico and Utah. The holotype of Neurankylus torrejonensis is the youngest known specimen of the Neurankylus lineage, which is known to reach at least back to the Late Cretaceous (Santonian). A nearly complete species-level analysis of baenids confirms the basal placement of Neurankylus outside of Baenodda and the split of Baenodda into two primary subclades, herein named Palatobaeninae and Eubaeninae.